AN ANALYSIS OF FIGURATIVE LANGUAGE ON THE SONG LYRIC â€œSTYLEâ€ BY TAYLOR SWIFT - Happy Saraswati Nurcahyanti; Novita Al Ihyak Dieni (LINGUAMEDIA Journal, 2025)
ABSTRACT This study entitled An Analysis of Figurative Language on the Song Lyric â€œStyleâ€ by Taylor Swiftâ€™s aims to find out the types of figurative language used in Taylor Swift lyrics and to describe the contextual meaning of the figurative language used in Taylorâ€™s lyrics. The research data was obtained from Taylor Swiftâ€™s song entitled Style. This study uses a qualitative descriptive method such as observation and library research in collecting research data. The researchers used qualitative theory which goes through a series of steps and iterations: gathering data, examining data, comparing prior data to newer data and developing new data to gather. After analyzing and discussing the lyrics of the song titled Style by Taylor Swift, the researchers can conclude that there are many types of figurative language found in this study. In this study, figurative language found is personification, metaphor, imagery, symbolism, repetition, allusion, consonance and irony. Thus, we can see that the listeners of the song can interpret a song better. Keywords: figurative language, qualitative, descriptive analysis, song.